2019
DOI: 10.1900/rds.2019.15.35
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physical Exercise on Gut Microbiome, Inflammation, and the Pathobiology of Metabolic Disorders

Abstract: BACKGROUND: The gastrointestinal tract (GIT) harbors a complex and diverse microbial composition that outnumbers our own body cells and their gene contents. These microbes play a significant role in host metabolism and energy homeostasis. Emerging evidence suggests that the GIT microbiome significantly contributes to host health and that impairments in the microbiome may cause the development of metabolic diseases. The microbiome architecture is shaped by several genetic and environmental factors, including nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 89 publications
3
57
1
1
Order By: Relevance
“…Here we observed that microbial community diversity, as revealed by alpha-and beta-diversity indexes were not signi cantly different between the study groups. These observations resemble with our previous ndings [9], where we report no statistical differences between the salivary microbiome diversity of obese pre-diabetic and healthy lean controls. Contrary to our observations, many researchers hypothesize that the diabetic phenotype is associated with a decline in gut microbial diversity, characterized as species richness and abundance [8,17,37].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Here we observed that microbial community diversity, as revealed by alpha-and beta-diversity indexes were not signi cantly different between the study groups. These observations resemble with our previous ndings [9], where we report no statistical differences between the salivary microbiome diversity of obese pre-diabetic and healthy lean controls. Contrary to our observations, many researchers hypothesize that the diabetic phenotype is associated with a decline in gut microbial diversity, characterized as species richness and abundance [8,17,37].…”
Section: Discussionsupporting
confidence: 93%
“…These studies concluded that diverse gut microbiome could have a protective effect against systemic in ammation and metabolic disorders. Similarly, no difference was observed between Firmicutes to Bacteroidetes ratio in the study groups, another critical parameter, most often emphasized as a prodrome for metabolic disorders development [9]. However, no signi cant differences in quanti cations of taxonomic composition at phylum were observed in this study among the study groups.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Numerous reviews have been published highlighting the effect of exercise on the gut microbiota (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). However, the primary focus of these reviews has been the implications for aspects of host health, such as the immune system and risk of chronic diseases.…”
Section: Methodsmentioning
confidence: 99%
“…Hyperglycemia in the pre-diabetic stage is correlated with obesity, blood pressure, and dyslipidemia [4]. However, like diabetes, obesity also does not have a well-defined etiology or pathogenesis and, in many cases, obesity is considered as a prodrome of insulin resistance (IR) in diabetes [5].…”
Section: Introductionmentioning
confidence: 99%